THE COMPATIBILITY STUDENT CHOICE OF UNIVERSITY MAJORING; A PRELIMINARY STUDIES - Daharnis, Daharnis; Ardi, Zadrian (Universitas Muhammadiyah Metro, 2016)
The continuous improvements in order to optimize the basic education to higher education are still running. Based on that purpose, there are many factors to supporting the students' learning activities success; one of the factors is suitability with majors in university. The purpose of this study is to reveal the condition of the compatibility of students majoring with their interest, then to describe the information when the student choose their majoring. Samples in this study were 122 peoples, taken by random sampling from the Padang State University. Data obtained by distributing questionnaires. The results showed that there are students that their major do not match with their interest (22.13%), only 3.28% of students who feel compatible with their major. This result should be a major concern, particularly for counselor in schools for design counseling services to solve these problems. The result of this study used as a grand tour or a preliminary study for further research.